La concentration et la propriété mixte des entreprises culturelles et des médias d’information au Canada - Yves Théorêt (Communication)
State intervention into concentration and mixed ownership of cultural ventures and news media derives mainly from two a priori assumptions: one views communication and democracy as intimately linked, and the other sees the private sector as primarily motivated by profit. In the past, these a priori assumptions guided the policies of occidental democracies, including Canada's. In an ever-changing world made up largely of market discourse, these assumptions seem out dated. Today, the government of Canada favours the creation of gigantic enterprises as if no regulation exists, and as such, ignores it's interventionist traditions and consequently, the "reasonable doubts" of those who worry about the negative impact of concentration and mixed ownership in cultural ventures and news media upon the quality and plurality of news content.